The Effect of Na-Based Salts on Critical Aggregation Concentration of Aqueous Peg-Sds Mixtures - Kulsum, U; Haque, MM; Akter, K; Gosh, RC (Bangladesh Journal of Physics, 2022)
Critical aggregation concentration (CAC) is a well-known parameter used to study the interactions between constituents in an aqueous mixture containing surfactant molecules. In this study, we have studied the effect of Na-based salts on CAC of aqueous binary mixture of neutral polymer, polyethylene glycol (PEG) and anionic surfactant, sodium dodecyl sulfate (SDS) using viscometric method. To estimate CAC, we have applied Jiang model to the measured viscosity data. From the estimated results, we observe that the value of CAC decreases with the increase of salt molecules in the mixtures. This behavior confirms that the presence of salt molecules favors the binding of SDS molecule to the PEG chain. Bangladesh Journal of Physics, 27(2), 39-48, December 2020